2000
DOI: 10.1074/jbc.c000606200
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Rescue of a Mutant Protein-tyrosine Kinase

Abstract: Protein-tyrosine kinases contain a catalytic loop Arg residue located either two or four positions downstream of a highly conserved Asp residue. In this study, the role of this Arg (Arg-318) in the protein-tyrosine kinase Cterminal Src kinase (Csk) was investigated. The observed k cat for phosphorylation of the random copolymer poly(Glu,Tyr) substrate by Csk R318A is ϳ3000-fold smaller compared with that of wild type Csk, whereas the K m values for ATP and poly(Glu,Tyr) are only mildly affected. The k cat valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
64
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(68 citation statements)
references
References 34 publications
4
64
0
Order By: Relevance
“…Because Csk phosphorylation of kdSrc is highly sensitive to ionic inhibition (data not shown), we first focused on 14 polar and charged residues (Arg-279, Arg-281, Arg-283, Glu-303, Arg-318, Asp-325, Ser-331, Lys-337, Asp-344, Lys-362, Ser-381, Lys-393, Lys-401, and Glu-438). Among the 14, Ser-331 is buried in the interior of Csk, and Arg-318, Lys-337, and Asp-344 have been previously excluded as possible residues to interact with Src (24,34,35), leaving 10 residues as potentially part of the substrate-docking site. No obvious spatial pattern was observed when the uniquely conserved residues were mapped onto the tertiary structure of Csk.…”
Section: Resultsmentioning
confidence: 99%
“…Because Csk phosphorylation of kdSrc is highly sensitive to ionic inhibition (data not shown), we first focused on 14 polar and charged residues (Arg-279, Arg-281, Arg-283, Glu-303, Arg-318, Asp-325, Ser-331, Lys-337, Asp-344, Lys-362, Ser-381, Lys-393, Lys-401, and Glu-438). Among the 14, Ser-331 is buried in the interior of Csk, and Arg-318, Lys-337, and Asp-344 have been previously excluded as possible residues to interact with Src (24,34,35), leaving 10 residues as potentially part of the substrate-docking site. No obvious spatial pattern was observed when the uniquely conserved residues were mapped onto the tertiary structure of Csk.…”
Section: Resultsmentioning
confidence: 99%
“…The kinase (proteintyrosine kinase C-terminal Src kinase) has an active site that pairs an aspartate with a nearby arginine (four residues away) and looks remarkably like the active site of Pus1p. Earlier work had shown that chemical rescue of a mutant enzyme, that replaces the arginine with alanine, was possible and that the class of small molecules that might restore activity could be predicted given knowledge of the composition of the active site (Williams et al 2000;Zhao et al 2004a). By understanding the topography of the active site of hPus1p and determining the flexibility of the requirements for particular amino acids that compose it, the pathway to identifying a class of compounds that could be considered for recovery of mutant hPus1p activity might be less uncertain.…”
Section: Modification Of Uridine At Position 30mentioning
confidence: 99%
“…It has previously been shown that the catalytic activity of an inactive Csk mutant, CskR318A, can be rescued by chemical compounds such as imidazole in vitro and in vivo (30,46). Csk −/− MEF cells transfected with the inactive CskR318A failed to show the characteristic inhibitory action of serum and LPA on ANP-stimulated GC-A activity.…”
Section: Discussionmentioning
confidence: 99%
“…In order to determine if the catalytic activity of Csk is essential for its inhibitory effect on GC-A, we used Csk −/− cells stably expressing the Csk R318A mutant whose catalytic activity is impaired but can be chemically rescued and activated by small organic compounds such as imidazole (30,46). Using this mutant cell line, we previously demonstrated that the catalytic activity of Csk is required for LPA-and serum-induced cytoskeletal reorganization in MEF cells (30).…”
Section: The Catalytic Activity Of Csk Is Essential For Its Regulatiomentioning
confidence: 99%